Effects of blackberry (Morus nigra) fruit juice on levodopa-induced dyskinesia in a mice model of Parkinson's disease - Fahimi Z; Jahromy MH (Dove Medical Press, 2018)
Zahra Fahimi, Mahsa Hadipour Jahromy Herbal Pharmacology Research Center, Department of Pharmacology, Faculty of Medicine, Tehran Medical Sciences Branch, Islamic Azad University, Tehran, Iran Background and objective: Levodopa-induced dyskinesia (LID) is a movement disorder that occurs due to levodopa consumption for a long period to attenuate Parkinsonism. Plants have been the basis for medical treatments in human history and still widely practiced. Blackberry (Morus nigra) is one of the fruits rich in anthocyanin. The present study examined the effect of blackberry fruit juice on LID in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease in mice.Materials and methods: In this study, 42 male mice were used, which were divided into six groups equally: one control group and five groups receiving MPTP injection. After confirmation of Parkinsonism in MPTP groups, one group was preserved without treatment and four other groups were treated with levodopa (50 mg/kg ip). After the onset of LID (2 weeks), one group was kept without additional treatment and three other groups were treated with three different doses of blackberry fruit juice (5, 10, and 15 mL/kg) with levodopa orally for 7 days. Abnormal involuntary movement scale (AIMS) and cylinder behavioral test were carried out according to the schedule. The collected data were analyzed using the SPSS software with the significant level of P<0.05.Results: Parkinson’s disease was confirmed with AIMS test on the fourth day after MPTP injection. The onset of LID was observed after 2 weeks of levodopa treatment using both behavioral tests. The result of administration of M. nigra fruit juice for 1 week showed that this addition is useful in hindering LID. These effects were more pronounced at doses 10 and 15 mL/kg with nearly the same results on attenuating AIMS. Low dose of the fruit juice does not seem to affect LID significantly.Conclusion: M. nigra fruit juice is effective to attenuate LID in an MPTP-induced Parkinson mice model. Keywords: Morus nigra, Parkinsonism, levodopa, LID, mice